2013
DOI: 10.1097/scs.0b013e318293f860
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Robotic Retropharyngeal Lymph Node Dissection With or Without Lateral Oropharyngectomy

Abstract: Retropharyngeal lymph node (RPLN) metastases can occur from advanced head and neck malignancies. Surgical access to RPLNs can be challenging. Considering the more aggressive conventional approach methods, there is an increasing need for minimally invasive techniques. Applying transoral robotic surgery (TORS) to access the RPLN has never been reported in the literature. The purpose of this study was to describe our experience with transoral robotic RPLN dissection for oropharyngeal and hypopharyngeal squamous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
(21 reference statements)
0
30
0
1
Order By: Relevance
“…If desired, an angled view can also be obtained through a beveled endoscopic camera. These all can be very helpful in identifying and preserving adjacent neurovascular structures of the retropharyngeal and parapharyngeal spaces while maximizing and the adequacy of resection [12,13,20,21]. The ease of use of the articulating robot instrument arms coupled with the 3-dimensional optics of the camera gives the surgical robot advantages over the use of an endoscope (that has a 2 dimensional view) and long transoral non-articulating instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If desired, an angled view can also be obtained through a beveled endoscopic camera. These all can be very helpful in identifying and preserving adjacent neurovascular structures of the retropharyngeal and parapharyngeal spaces while maximizing and the adequacy of resection [12,13,20,21]. The ease of use of the articulating robot instrument arms coupled with the 3-dimensional optics of the camera gives the surgical robot advantages over the use of an endoscope (that has a 2 dimensional view) and long transoral non-articulating instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision of isolated retropharyngeal lymph node metastases from WDTC has been well described via trans-cervical, trans-mandibular, and trans-oral approaches, including endoscopic-assisted trans-oral resection [5][6][7][8][9][10][11]. Trans-oral robotic surgery (TORS) has been described for excision of metastatic retropharyngeal lymph nodes of oropharyngeal carcinoma and of parapharyngeal space tumors, but never for an isolated retropharyngeal metastasis from WDTC [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Shellenberger et al [10] reported 3 cases of differentiated thyroid carcinoma safely removed by a transoral approach guided by preoperative ultrasonography. Byeon et al [11] also reported the removal of parapharyngeal tumors by transoral robotic surgery. Liu et al [13] noted the usability of intraoperative cone beam CT guidance with transoral robotic surgery in the oropharyngeal region of porcine and cadaveric models.…”
Section: Discussionmentioning
confidence: 99%
“…The key to successfully operate RPS lesions is to ensure an adequate surgical field as well as an adequate view enabling the identification of surrounding vital nerves and vessels. Surgical approaches to the RPS are classified as transcervical [5] or transoral [9,10,11]. A transcervical approach is conventionally chosen as an extension of neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic involvement of the RPLN occurs in approximately 10-16 % of OPSCC patients, is associated with more advanced disease, and confers a worse prognosis [22,23]. More recently, Byeon et al [24] reported on the feasibility of TORS RPLN dissection with or without lateral oropharyngectomy, a technique that has also been applied to the resection of RPLN metastases from papillary thyroid cancer [25]. The authors commented that TORS along with a detailed knowledge of the anatomy offers a minimally invasive technique for removing pathologic nodes while preserving the surrounding neurovascular structures.…”
Section: Current Indicationsmentioning
confidence: 98%